(untitled) (Research, Society and Development, 2021)
Fiberglass pins or fused metal cores are used in dentistry as intraradicular retainers and have the main purpose of replacing the lost dental structure, in addition to facilitating the support and retention of the crown. The purpose of the review was to analyze the literature in relation to the comparison between fiber pins and fused metal cores. An integrative literature review was developed in the SciELO and LILACS databases, using the descriptors: “Mouth Rehabilitation”, “Dental pins” and “Post and Core Technique” individually and then the crossing with the Boolean operator AND. The inclusion criteria used in the selection of articles were: articles published in Portuguese available in full that portrayed the problem researched, articles published and indexed in the referred databases in the last fifteen years (2005 to 2020). Twenty articles were found and from them it was verified that the use of fused metal cores is decreasing, due to the success of aesthetic pins. Root fracture is less in teeth restored with fiberglass pins due to the better distribution of forces. Despite this, it is a fact that both fused metal cores and fiberglass pins have good results when used correctly, but fiberglass pins have greater resistance to fracture. Further studies can be done with several brands in use in the market, to better guide the dentist about the materials in use.